Neonates and COVID-19: state of the art: Neonatal Sepsis series - Ryan, L.; Plötz, F.B.; van den Hoogen, A.; Latour, Jos; Degtyareva, M.; Keuning, M.; Klingenberg, C.; Reiss, I.K.M.; Giannoni, E.; Roehr, C.; Gale, C.; Molloy, E.J. (2022)
Abstract: The SARS-CoV-2 pandemic has had a significant impact worldwide, particularly in middle- and low-income countries. While this impact has been well-recognized in certain age groups, the effects, both direct and indirect, on the neonatal population remain largely unknown. There are placental changes associated, though the contributions to maternal and fetal illness have not been fully determined. The rate of premature delivery has increased and SARS-CoV-2 infection is proportionately higher in premature neonates, which appears to be related to premature delivery for maternal reasons rather than an increase in spontaneous preterm labor. There is much room for expansion, including long-term data on outcomes for affected babies. Though uncommon, there has been evidence of adverse events in neonates, including Multisystem Inflammatory Syndrome in Children, associated with COVID-19 (MIS-C). There are recommendations for reduction of viral transmission to neonates, though more research is required to determine the role of passive immunization of the fetus via maternal vaccination. There is now considerable evidence suggesting that the severe visitation restrictions implemented early in the pandemic have negatively impacted the care of the neonate and the experiences of both parents and healthcare professionals alike. Ongoing collaboration is required to determine the full impact, and guidelines for future management. Impact: Comprehensive review of current available evidence related to impact of the COVID-19 pandemic on neonates, effects on their health, impact on their quality of care and indirect influences on their clinical course, including comparisons with other age groups.Reference to current evidence for maternal experience of infection and how it impacts the fetus and then neonate.Outline of the need for ongoing research, including specific areas in which there are significant gaps in knowledge.